Intergeneration learning as a dialog in overcoming loneliness of older adults - Irena Žemaitaitytė; Jolanta Pivorienė; Raminta Bardauskienė; Agata Katkonienė (Ricerche di Pedagogia e Didattica, 2023)
Increasing life expectancy and inclusion of older people in care system changes the intergenerational communication. Various professionals such as social workers and caregivers take care of older people needs. Little attention is paid to intergenerational learning and education in social care organizations despite it may help to overcome feeling of loneliness among older people. Loneliness is a negative emotion associated with a perceived gap between existing relationships and desired ones. It is widely recognized as one among the most significant and entrenched issues facing our aging society. The effect of loneliness is harmful to health and increases the risk of disability. Intergenerational links have been identified as an important issue in elderly care. Educational activities for the elderly are offered in various social care institutions in Lithuania. The research data reveal several predominant topics that would be relevant to older learners, such as loneliness, activity of older people, and communication.